Movement Disorders in Women - Baker, Jessica M.; Hung, Albert Y. (Seminars in Neurology, 2017)
Movement disorders such as Parkinson's disease (PD), restless legs syndrome (RLS), chorea, essential tremor, and Tourette syndrome, occur in men and women of all ages. Yet, considerable sex differences in epidemiology, clinical features, and treatment exist in these disorders. In this review, we highlight key differences in the evaluation and management of women with movement disorders, addressing sex-specific complications of treatment and unique challenges surrounding the management of movement disorders during pregnancy. We review the complex relationship between estrogen and movement disorders, including the putative neuroprotective effects of estrogen in PD and the modulatory effects on RLS and chorea associated with autoimmune disease. Further understanding of sex-specific and hormonal effects on clinical features will be important to optimize the management of women with movement disorders in the future.
Keywords: Parkinson's disease; restless legs syndrome; Tourette syndrome; chorea gravidarum; essential tremor; estrogen; sex differences; pregnancy